Plant Growth Regulators INCYDE and TD-K Underperform in Cereal Field Trials - Matthew J. van Voorthuizen (MDPI AG, 2021)
Using plant growth regulators to alter cytokinin homeostasis with the aim of enhancing endogenous cytokinin levels has been proposed as a strategy to increase yields in wheat and barley. The plant growth regulators INCYDE and CPPU inhibit the cytokinin degrading enzyme cytokinin oxidase/dehydrogenase (CKX), while TD-K inhibits the process of senescence. We report that the application of these plant growth regulators in wheat and barley field trials failed to enhance yields, or change the components of yields. Analyses of the endogenous cytokinin content showed a high concentration of trans-zeatin (tZ) in both wheat and barley grains at four days after anthesis, and statistically significant, but probably biologically insignificant, increases in cisZ-O-glucoside, along with small decreases in cZ riboside (cZR), dihydro Z (DHZ), and DHZR and DHZOG cytokinins, following INCYDE application to barley at anthesis. We discuss possible reasons for the lack of efficacy of the three plant growth regulators under field conditions and comment on future approaches to manipulating yield in the light of the strong homeostatic mechanisms controlling endogenous cytokinin levels.